Improving Corn Processing Skills For Women Corn Farmers In Warbo Village, Arso 7 District, West Arso, Keerom Regency, Papua - Lisye Iriana Zebua; Farmawaty Farmawaty; Triwiyono Triwiyono; Ade Nancy Wambrauw; Nurhidayah Septia; Nia Rahmadani (International Journal of Community Service (IJCS), 2026)
Corn is an important commodity in Keerom Regency, especially in Arso District, which is one of Indonesia's corn production centers. Several corn production centers in Indonesia include Jayapura Regency (Nimbokrang), Keerom-Arso Regency, and Jayapura City (West Koya). The problems are 1) corn utilization is limited to consumption or sale in the market to supplement family income; 2) lack of information about corn-based product diversification in Warbo-Arso 7 Village, West Arso District, Keerom Regency due to a lack of technological information and limited community knowledge and skills regarding corn product diversification Based on the above issues, the specific objectives of this community service activity are: 1) to introduce high-value corn-based food products to the people of Kampung Warbo and 2) to train corn-farming mothers and young women to process various types of corn-based food products. The community service method that will be used in this training consists of five stages, namely 1) Preparation; 2) Counseling; 3) Brief practice; 4) Assistance; and 5) Evaluation. The evaluation of activities was conducted before and after implementation, namely through interviews and questionnaires filled out by participants. Based on the results of the post-test on corn processing, 85% of participants were able to understand and absorb the material on corn processing. After the training, 90% of participants were skilled in processing corn flour, corn milk, and corn-based noodles. Then, participants can understand and practice creative and innovative ways of packaging corn products. Keywords: Corn, milk, noodles, skills, flour